The Impact of COVID-19 Fatigue and Pandemic Burnout alongside Academic Stress on the Gingival Health of Dental Students - Ali, Jameela; Al-ruwais, Mathayel; Jawa, Shahad; Ahmed, Yara; Babatin, Wafaa; Abdelrasoul, Mohammed Roshdy (European Journal of General Dentistry, 2024)
Objectives Stress has delirious effects on gingival health. Dental students experience higher levels of academic stress during their education that requires clinical and patient management skills. Coronavirus disease 2019 (COVID-19) fatigue is a type of chronic stress that has put the population under high stress for an extended period of time. This study aimed to assess the impact of pandemic burnout and fatigue on the gingival health of academically stressed dental students.Materials and Methods This study compared junior (n = 20) and senior (n = 20) year dental students undergoing their final year exams. Gingival health was assessed by plaque index (PI), gingival index (GI), and modified papillary bleeding index (MPBI). Academic stress was measured by the dental environmental stress questionnaire, while COVID-19 burnout was judged by COVID-19 student stress questionnaire (CSSQ).Statistical Analysis Quantitative data were expressed as mean, standard deviation and median Student's t-test was used to compare two categories for normally distributed quantitative variables, while significance of the obtained results was judged at the 5% level.Results Gingival health evaluation revealed no significant differences in GI and PI; however, MPBI in juniors was more significant (p = < 0.001). Academic stress was significantly higher among seniors (p = 0.001); nevertheless, CSSQ showed low levels of stress toward the pandemic with no significant differences.Conclusion Gingival diseases are multifactorial in nature; stress is a biologically influencing factor as well. Despite the evidence of high academic stresses among dental students, the impact of COVID-19 fatigue on gingival health was inconclusive and slight differences were found between junior and senior-year dental students.
Keywords: academic; COVID-19; dental students; gingiva; stress